Socioeconomic Status Impact on Diet Quality and Body Mass Index in Eight Latin American Countries: ELANS Study Results - Gómez, Georgina (Nutrients, 2021)
Poor health and diet quality are associated with living within a low socioeconomic status (SES). This study aimed to investigate the impact of SES on diet quality and body mass index in Latin America. Data from the “Latin American Health and Nutrition Study (ELANS)”, a multi-country, population-based study of 9218 participants, were used. Dietary intake was collected through two 24 h recalls from participants of Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru and Venezuela. Diet quality was assessed using the dietary quality score (DQS), the dietary diversity score (DDS) and the nutrients adequacy ratio (NAR). Chi-squared and multivariate-variance analyses were used to estimate possible associations. We found that participants from the low SES consumed less fruits, vegetables, whole grains, fiber and fish and seafood and more legumes than those in the high SES. Also, the diet quality level, assessed by DQS, DDS and NAR mean, increased with SES. Women in the low SES also showed a larger prevalence of abdominal obesity and excess weight than those in the middle and high SES. Health policies and behavioral-change strategies should be addressed to reduce the impact of socioeconomic factors on diet quality and body weight, with gender as an additional level of vulnerability.